Pentingnya Lingkungan Yang Nyaman Untuk Belajar - Nurfitria Safina Syakila; Jasiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
A comfortable learning environment plays an important role in supporting the success of the learning process. A clean, safe, quiet, and conducive environment can improve students’ concentration, motivation, discipline, and learning outcomes. This article aims to describe the importance of a comfortable learning environment for students’ learning success. The method used in this study is a literature review by examining various scientific sources related to the learning environment. The results of the study indicate that both physical and social learning environments greatly influence students’ learning effectiveness. A supportive learning environment can create a pleasant learning atmosphere and encourage students to participate actively in the learning process. On the other hand, an uncomfortable environment, such as noisy classrooms, inadequate facilities, and poor social relationships, can hinder students’ concentration and reduce learning effectiveness. Therefore, cooperation between schools, teachers, parents, and the community is needed to create a comfortable and conducive learning environment so that learning objectives can be achieved optimally.